PENGARUH FRAUD TRIANGLE TERHADAP KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Andriani, Rosedian (JURNAL RISET AKUNTANSI TIRTAYASA, 2019)
This study aims to examine the influence of Fraud Triangle on Fraudulent Financial Statement. Fraudulent Financial Statement in this study used Beneish m-score index. Fraud Triangle measured by three perspective; pressure (solvency ratio), opportunity (asset turnover ratio) and rationalization (profitability ratio).The Sample used were 90 manufacture companies listed on Indonesia Stock Exchange in 2015-2017, using purposive sampling method. Sample were then analyzed using logistic regression analysis. The result of this analysis is pressure (solvency ratio) not significantly affect fraudulent financial statement. Furthemore, opportunity have positive effect on fraudulent financial statement and rationalization (profitability ratio) have negative effect on fraudulent financial statement.Â Keywords : fraudulent financial statement, fraud triangle, beneish m-score indexÂ